The Effect of The Experimentally Induced Hypothyroidism on Thyrotrophs, Somatotrophs and Mammotrophs in The Rat Pituitary - Kükner, Aysel; Öner, Jale; Çolakoğlu, Neriman; Öner, Hakan; Özoğul, Candan; Ozan, Enver (Fırat University, 2003)
Aim: The purpose of this study was to describe the morphologic alterations in somatotrophs, thyrotrophs and mammotrophs cells during evolution and regression of hypothyroidism. Material and method: Eight rats were rendered hypothyroid by administration of 10mg/kg, intraperitoneally PTU (6-n-propyl-2-thiouracil). Four rats were sacrificed after 15 days of PTU administration. The other four rats were sacrificed on 15 days after interruption of PTU administration. Pituatary glands of anterior lobe was dissected and fixed in 2.5% glutaraldehyde in phosphate buffer. Semi-thin and ultrathin sections were determined by light and electron microscope. Results: It was observed that numerous thyroidectomy cells with vacuolated cytoplasm in the adenohypophysis on the 15 days of PTU treatment rats. In the thyroidectomy cells the extreme dilation of the abundant RER and reduced of the secretory granules. Intracisternal granules the characteristic markers of thyroidectomy cells. Some somatotroph cells had a little dilated RER, but some of them had very large dilated RER structure and reduced of the secratory granules. Mammotroph cells generally similar to control group. It was observed that thyroidectomy cells reduced after 15 days interruption of PTU treatment. Some somatotrophs still had dilated RER. Conclusion: In the experimental hypothyroidism, it was observed that number of thyroidectomy cells increased. Administration of PTU affected both somatotrophs and mammotrophs cells, but particulary somatotrophs. After interruption of drug adenohyphsis structure was showed similarity with control group.

Amaç: Bu çalışmanın amacı hipotiroidizm gelişimi ve gerilemesi sırasında somatotrop, tirotrop ve mammotrop hücrelerindeki yapısal değişikliklerin ayırt edilmesidir. Gereç ve yöntem: Sekiz sıçana 10mg/kg, periton içi propil tiourasil (PTU) verilerek hipotiroidi oluşturuldu. PTU verildikten 15 gün sonra 4 sıçan öldürüldü. Diğer 4 sıçan ise PTU verilmesi kesildikten 15 gün sonra kesildi. Hipofiz bezinin ön lobu ayrıldı, fosfat tamponlu % 2.5 lik glutaraldehit ile tespit edildi. Yarı ince ve ince kesitler ışık ve elektron mikroskop ile incelendi. Bulgular: On beş gün PTU verilen sıçan adenohipofizlerinde vakuolize sitoplazmalı çok sayıda tiroidektomi hücresi gözlendi Tiroidektomi hücrelerinde bol miktarda GER ve azalmış salgı granülleri vardı. Sisternalar içindeki granüller Tiroidektomi hücrelerinin karakteristik özellikleriydi. Bazı somatotrop hücreler az miktarda genişlemiş GER yapılarına, bazıları ise oldukça genişlemiş GER ve azalmış salgı granüllerine sahipti. Mammotrop hücreleri genellikle kontrol grubuna benziyordu. PTU verilmesi kesildikten 15 gün sonra tiriodektomi hücreleri azalmıştı. Bazı somatotrop hücrelerde hala genişlemiş GER yapıları vardı. Sonuç: Deneysel hipotiroidizmde tiroidektomi hücrelerinin sayısında artış gözlendi. PTU uygulaması özellikle somatotrop hücreleri olmak üzere hem somatotrop hem de mammotropları etkiledi. İlaç uygulamasının kesiminden sonra adenohipofiz yapısı kontrol grubu ile benzerlik gösterdi.
Deneysel Oluşturulan Hipotiroidizmin Sıçan Hipofizindeki Tirotrop, Somatotrop ve Mammotroplara Etkisi